Shakespeare and the Cultural Capital Tension: Advancing Literacy in Rural Arkansas. - Jolliffe, David A. (Community Literacy Journal)
A multi-faceted Shakespeare festival in a small town in rural east central Arkansas, part of a larger Community Literacy Advocacy Project, represents a concerted effort to alter the discourse of decline in this economically troubled region, but it also raises some challenging issues about how such projects distribute social and cultural capital among their participants.